Translating Research into Practice in Nursing Homes: Can We Close the Gap? - Rahman, Anna N. (Oxford University Press, 2012)
Purpose: A gap between research and practice in many nursing home (NH) care areas persists despite efforts by researchers, policy makers, advocacy groups, and NHs themselves to close it. The reasons are many, but two factors that have received scant attention are the dissemination process itself and the work of the disseminators or change agents. This review article examines these two elements through the conceptual lens of Roger’s innovation dissemination model. Design and Methods: The application of general principles of innovation dissemination suggests that NHs are characteristically slow to innovate and thus may need more time as well as more contact with outside change agents to adopt improved practices. Results: A review of the translation strategies used by NH change agents to promote adoption of evidence-based practice in NHs suggests that their strategies inconsistently reflect lessons learned from the broader dissemination literature. Implications: NH-related research, policy, and practice recommendations for improving dissemination strategies are presented. If we can make better use of the resources currently devoted to disseminating best practices to NHs, we may be able to speed NHs’ adoption of these practices.